Impact of FDI on industrial structure upgrading under green technology innovation in Jiangsu, China - Wang, Shijin; Zhou, Huiying; Tian, Keqin (Journal of environmental engineering and landscape management, 2023)
Industrial structure upgrading plays an important role in improving economic development efficiency. Taking Jiangsu as the study subject, the paper selects panel data from 2005 to 2018 and performs dynamic panel models and threshold models to analyze the influence mechanism of foreign direct investment (FDI) and green technology innovation on industrial structure upgrading (including rationalization and advancement). The results show that FDI acts negatively on industrial structure upgrading, exhibiting U-shaped relationship with advancement, in contrast, green technology innovation shows a positive contribution to upgrading. In addition, rationalization is limited by fixed assets growing but increases with rising education levels. An increase in fixed assets and education both have a positive effect on advancement. Further, FDI plays a facilitating role in advancement considering the positive moderating effect of green technology innovation. Therefore, the study provides a theoretical reference for the development path of foreign investment and industrial structure upgrade breakthrough in Jiangsu.